Oldest high-Ti basalt and magnesian crustal materials in feldspathic lunar meteorite Dhofar 1428. (1st December 2019) - Xue, Zhuqing; Xiao, Long; Neal, Clive R.; Xu, Yigang
Highlights: Multiple clasts including high-Ti basalt were found in this meteorite. In situ dating shows it is one of the earliest high-Ti basalts on the Moon. Enriched magmas with different REE patterns relative to KREEP existed on the Moon. Abstract: We conducted a thorough analysis of the feldspathic breccia meteorite Dhofar 1428 with the aim of better understanding the composition and evolution of lunar crust. This sample comprises a heterogeneous array of lithic fragments including magnesian and ferroan anorthositic granulites, mafic granulites/granulitic breccia, basalts, and different kinds of impact melt rocks. In which, a high-Ti basalt clast comprising large zoned pyroxene was observed. Based on equilibrium melt calculations of mineral zonations from this basalt, Mg-pyroxene cores were interpreted to be formed from a light rare earth element (LREE) enriched liquid, whereas the Fe-pyroxene rims grew from an LREE-depleted magma. We propose that LREE-depleted signature of Fe-pyroxene results from co-crystallization with apatite. The Mg-pyroxenes suggest that enriched liquids with higher REE contents and different REE patterns relative to KREEP existed within lunar interior. Oscillating Ti/Al ratios across pyroxene in this basalt may indicate several magma recharge events or crystal movement within a zoned magma chamber. This feature illustrates that magmas were derived from a variety of sources around the time of formation of this basalt. In situ U-Pb dating was conducted on apatite grains within this basalt, the excellent consistence between the U-Pb Concordia age (3941 ± 24 Ma, 2σ) and 207 Pb/ 206 Pb isochron age (3934 ± 24 Ma, 2σ) indicates the most likely crystallization age of this high-Ti basalt at ∼3940 Myr, making it one of the oldest high-Ti basalts formed on the Moon. Magnesian anorthositic granulites are mineralogically and geochemically similar to those trace element-poor magnesian anorthositic granulites in many lunar meteorites. These magnesian granulites cannot form from simple mixing of pristine Ferroan Anorthosite and lithologies from the Mg-Suite, and do not have any affinities with KREEP or the Procellarum KREEP Terrane, and they could be important components of farside highlands.